2011
DOI: 10.1016/j.neubiorev.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias in neuroscience and biomedical research

Abstract: Female mammals have long been neglected in biomedical research. The NIH mandated enrollment of women in human clinical trials in 1993, but no similar initiatives exist to foster research on female animals. We reviewed sex bias in research on mammals in 10 biological fields for 2009 and their historical precedents. Male bias was evident in 8 disciplines and most prominent in neuroscience, with single-sex studies of male animals outnumbering those of females 5.5 to 1. In the past half-century, male bias in non-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
1,131
2
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 1,380 publications
(1,183 citation statements)
references
References 56 publications
34
1,131
2
16
Order By: Relevance
“…The latter observation is in line with human studies that documented symptoms of schizophrenia are most severe during the late luteal and premenstrual phases, when estrogen levels are low (Angermeyer et al, 1998;Hafner et al, 1993). More importantly, since sex steroids play an important modulatory role in the regulation of immune function, and a variety of autoimmune (e.g., rheumatoid arthritis, Grave's disease) and neurological (e.g., anxiety, depression) disorders are more prevalent in females than males (reported in (Beery and Zucker, 2011;Gaillard and Spinedi, 1998), it is necessary to remove sex bias from neuroscience and biomedical sciences in general.…”
Section: Male Bias In the Neurosciencessupporting
confidence: 74%
See 4 more Smart Citations
“…The latter observation is in line with human studies that documented symptoms of schizophrenia are most severe during the late luteal and premenstrual phases, when estrogen levels are low (Angermeyer et al, 1998;Hafner et al, 1993). More importantly, since sex steroids play an important modulatory role in the regulation of immune function, and a variety of autoimmune (e.g., rheumatoid arthritis, Grave's disease) and neurological (e.g., anxiety, depression) disorders are more prevalent in females than males (reported in (Beery and Zucker, 2011;Gaillard and Spinedi, 1998), it is necessary to remove sex bias from neuroscience and biomedical sciences in general.…”
Section: Male Bias In the Neurosciencessupporting
confidence: 74%
“…A survey of 2000 basic research papers in 2009 (Beery and Zucker, 2011) revealed a male bias in 8 out of 10 disciplines, most pronounced in neuroscience and pharmacology. What is more alarming is that many articles failed to report the sex of the subjects used and when both sexes were used in a study, about two-thirds of those studies did not analyze the data by sex (Beery and Zucker, 2011;Wald and Wu, 2010).…”
Section: Male Bias In the Neurosciencesmentioning
confidence: 99%
See 3 more Smart Citations